Blood Cell In Vitro Cytokine Production in Response to Lipopolysaccharide Stimulation in a Healthy Population: Effects of Age, Sex, and Smoking - Lluis Rodas; Sonia Martínez; Aina Riera-Sampol; Hannah J. Moir; Pedro Tauler (Cells, 2021)
Immune system functionality has been commonly assessed by a whole-blood or isolated-cell stimulation assay. The aim of this study was to determine whether cytokine production in whole-blood-stimulated samples is influenced by age, sex, and smoking. A descriptive cross-sectional study in 253 healthy participants aged 18–55 years was conducted. Whole blood samples were stimulated for 24 h with LPS and concentrations of IL-6, IL-10, and TNF-α were determined in the culture media. Among parameters considered, statistical regression analysis indicated that smoking (change in R2 = 0.064, p < 0.001) and sex (change in R2 = 0.070, p < 0.001) were the main predictors for IL-10 production, with higher values for women and non-smokers. Age was also found to be a significant predictor (change in R2 = 0.021, p < 0.001), with higher values for younger ages. Age (change in R2 = 0.089, p = 0.013) and smoking (change in R2 = 0.037, p = 0.002) were found to be negative predictors for IL-6 production. Regarding TNF-α-stimulated production, age (change in R2 = 0.029, p = 0.009) and smoking (change in R2 = 0.022, p = 0.022) were found to be negative predictors. Furthermore, sex (change in R2 = 0.016, p = 0.045) was found to be a significant predictor, with lower values for women. In conclusion, sex, age, and smoking were found to be independent determinants of stimulated cytokine production. While female sex is associated with higher IL-10 and lower TNF-α production, aging and smoking are associated with lower IL-6, IL-10, and TNF-α production.